Are Next-Generation Sequencing Tools Ready for the Cloud?. Issue 6 (June 2017) - Celesti, Antonio; Celesti, Fabrizio; Fazio, Maria; Bramanti, Placido; Villari, Massimo
Abstract : Cloud-based next-generation sequencing (NGS) tools are currently at an early stage. In this Forum article, we provide a clear picture of the current cloud-based NGS solutions and highlight what is still missing, along with future challenges for the achievement of an ecosystem of biotechnology clouds.